Preparation, Characterization and Luminescence of (MCM-41)-AgBr Nanocomposite Materials - Li, Xiao-Dong; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
MCM-41 was used as host for accommodating AgBr into the channels by three methods i.e., heat diffusion, microwave-assisted and ion exchange methods. A series of characterizations were used to characterize the prepared nanocomposites. When the content of AgBr was below 10 wt %, the results showed that the AgBr located in the channels of MCM-41 and the framework of the MCM-41 in the nanocomposites were not destroyed. Analyses of the luminescent properties of the (MCM-41)-AgBr were carried out and the emission peak shifted to the lower energy side with increasing loading density of AgBr, indicating that the AgBr were confined in the channels of MCM-41 and the quantum confinement effect in the AgBr nanoparticles as a consequence of their samll size. The (MCM-41)-AgBr prepared by microwave-assisted method had more intensity than the (MCM-41)-AgBr nanocomposites prepared by other method. The AgBr were successfully incorporated into the channels of MCM-41 and the prepared nanocomposites possessed interesting optical properties.